2015
DOI: 10.1016/j.renene.2014.11.088
|View full text |Cite
|
Sign up to set email alerts
|

Exploring impacts of process technology development and regional factors on life cycle greenhouse gas emissions of corn stover ethanol

Abstract: . (2015) Exploring impacts of process technology development and regional factors on life cycle greenhouse gas emissions of corn stover ethanol. Renewable Energy, 76 . pp. 726-734. ISSN 1879-0682 Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/33577/1/Tech%20development%20and%20regional %20factors%20ethanol%20Resub%20FINAL2.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 20 publications
4
21
0
Order By: Relevance
“…Regardless of the treatment pathway, enzyme production is a major contributor to the conversion‐related impacts for most categories. This is in line with other studies, which found life cycle results of lignocellulosic ethanol sensitive to impacts from enzyme provision (Gerbrandt et al, ; McKechnie et al, ; Wang, Littlewood, & Murphy, ). Related impacts are subject to uncertainty, as reported burdens for enzyme provision vary widely.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regardless of the treatment pathway, enzyme production is a major contributor to the conversion‐related impacts for most categories. This is in line with other studies, which found life cycle results of lignocellulosic ethanol sensitive to impacts from enzyme provision (Gerbrandt et al, ; McKechnie et al, ; Wang, Littlewood, & Murphy, ). Related impacts are subject to uncertainty, as reported burdens for enzyme provision vary widely.…”
Section: Discussionsupporting
confidence: 91%
“…Over the last decade, the potential to produce transportation fuels from lignocellulosic feedstocks has been accentuated (van der . This trend is supported by the advancement of conversion technologies and coincides with ambiguity in sustainability considerations of sugar-or starch-based biofuels (McKechnie, Pourbafrani, Saville, & MacLean, 2015). Controversies related to these first generation feedstocks include concerns about food competition, land use change or intensive agricultural inputs and have directed the research focus towards lignocellulose-based solutions (Falano, Jeswani, & Azapagic, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the overall life-cycle GHG emissions per unit of ethanol produced from corn stover were 245.5 kg of CO 2 -eq ton −1 , 738.7 g CO 2 -eq L −1 , or 34.7 g CO 2 -eq MJ −1 . The 34.7 g CO 2 -eq MJ −1 was similar to the value of 38.0 g CO 2 -eq MJ −1 , which was also based on the NREL bioethanol production process [44]. However, it was lower than the 65.3 g CO 2 -eq MJ −1 reported by Zhao et al [13] because the fertilizer quantity in this study was lower than in previously published studies.…”
Section: Discussionsupporting
confidence: 84%
“…Biomass Production, and Logistics: In this study, we considered corn stover as a representative feedstock for biofuel production. We assume that farmers replace the nutrient content of harvested corn stover by applying additional fertilizers, as is common practice in the most widely-cited models and studies [41][42][43] . Assumptions for corn stover yield, energy demand for harvesting, and additional fertilizer requirements are presented in Supplementary Information A (Table S1).…”
Section: Methodsmentioning
confidence: 99%